The DNA Damage Response Kinases DNA-dependent Protein Kinase (DNA-PK) and Ataxia Telangiectasia Mutated (ATM) Are Stimulated by Bulky Adduct-containing DNA - Kemp, Michael G. (American Society for Biochemistry and Molecular Biology, 2011)
A variety of environmental, carcinogenic, and chemotherapeutic agents form bulky lesions on DNA that activate DNA damage checkpoint signaling pathways in human cells. To identify the mechanisms by which bulky DNA adducts induce damage signaling, we developed an in vitro assay using mammalian cell nuclear extract and plasmid DNA containing bulky adducts formed by N-acetoxy-2-acetylaminofluorene or benzo(a)pyrene diol epoxide. Using this cell-free system together with a variety of pharmacological, genetic, and biochemical approaches, we identified the DNA damage response kinases DNA-dependent protein kinase (DNA-PK) and ataxia telangiectasia mutated (ATM) as bulky DNA damage-stimulated kinases that phosphorylate physiologically important residues on the checkpoint proteins p53, Chk1, and RPA. Consistent with these results, purified DNA-PK and ATM were directly stimulated by bulky adduct-containing DNA and preferentially associated with damaged DNA in vitro. Because the DNA damage response kinase ATM and Rad3-related (ATR) is also stimulated by bulky DNA adducts, we conclude that a common biochemical mechanism exists for activation of DNA-PK, ATM, and ATR by bulky adduct-containing DNA.